A Foucauldian critique of neo-liberalsim - Sachikonye, Tawanda (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2010)
This study attempts to make a contribution to the critique of contemporary capitalism. This has been conceptualised through a Foucauldian critique of neo-liberalism, that is, Foucault's concepts of power and governmentality have been used to criticise neo-liberalism. The study argues that neo-liberalism is a hegemonic and oppressive politico-economic social system. This has occurred in two ways; firstly, neo-liberalism came to dominate the global economy and, secondly, neo-liberalism has become the dominant politico-economic discourse. An attempt is made to expose the discourses and institutions that buttress the neo-liberal project by undertaking a Foucauldian critique. According to Foucault, knowledge shapes the social space through its 'mechanisms', discourses and institutions. In order to critique neo-liberalism, it is necessary to expose its power-knowledge base, which is what gives it legitimacy. By analysing and exposing neo-liberalism's power-knowledge base, its oppression becomes clear through an observation of the material effects of neo-liberal ideology and policy. This study also evaluates to what extent Marxism is a viable alternative to neo-liberalism, in order to ascertain what Foucault adds to already existing critiques of capitalism, and neo-liberalism, in particular. It concludes by arguing that even though Marxism provides a useful framework in which to understand neo-liberal domination, its labour based social theory is somewhat outdated in our contemporary age of the information society. Therefore, it is Foucault's concept of power-knowledge that is most pertinent in providing an effective critical theory of neo-liberalism in the age of the information society, as it focuses on the primacy of power-knowledge in matters of domination.
Keywords: Neoliberalism; Political science -- Philosophy; Philosophy, Marxist; Foucault, Michel, 1926-1984; Socialism; Capitalism